(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2022)
We are delighted to be part of TIPSCON 2022 11th National Conference organized by Trinity Institute of Professional Studies on the theme “Resilience & Reinvention a path for changing in the. Management, IT , Media & Law” .In contemporary times where national as well as international environment is too dynamic and vulnerable, law becomes an instrumental remedial tool to provide direction and sustainability to us. Thus, it becomes a foremost responsibility of legal professionals to highlight and work on the various dimensions of emerging trends in legal education. With growing advancement in Information and communication technologies, usage of Artificial Intelligence & applications the nuisances associated with it are also increasing therefore it becomes vitality to protect and safeguard the cyberspace & educate people about cyber security and laws. At the same time it is also important to deal with the development of new methodologies and scientific tools for purpose of investigation in Legal Education. Recognizing the role and leadership of legal community in this dynamism . This conference adds more significance to the fact and affirms the same. I am confident that the deliberations during the conference will be beneficial to all the participants and it would provide them a platform for sharing knowledge about the recent trends and advances in these domains.